Os efeitos da incorporação de resíduos de pneus nas propriedades de compósitos a base de geopolímero - Gratão, Leonardo Santos (2021)
Economic and population growth drive the extraction of natural resources intensely, harming the environment and human health. The construction industry uses a large amount of raw materials, energy, uses materials whose production emits polluting gases and also generates a large volume of waste. On the other hand, the construction sector has great potential to absorb various types of waste in the production of more sustainable building materials, thus minimizing the sector's impact on the environment. In this sense, this research proposes to evaluate the use of tire rubber waste in geopolymer mortar based on metakaolin activated with a solution of sodium silicate (12 M) and sodium hydroxide (15 M). For this purpose, the geopolymer mortar that will serve as a reference for all composites with a sand/metakaolin ratio of 2, water/metakaolin of 0.60 and Na2SiO3/NaOH of 2.5 was defined. For the analysis and optimization of these composites, central composite planning with 18 experiments was used to study the influence of the replacement content (by volume) of sand by rubber residues (1 to 20%), of the percentage (by mass) of coarse rubber residue (0 to 100%) and cure time (1 to 28 days). Properties such as compressive strength, water absorption, void ratio, specific mass, flexural modulus of rupture, modulus of elasticity and toughness of the produced geopolymer composites were evaluated. Furthermore, analyzes were performed by scanning electron microscopy, energy dispersive spectroscopy and x-ray diffraction to evaluate the microstructure and composition of the composites. With the analysis of the response surfaces, it was observed that the replacement of sand by rubber residue had little influence on the modulus of elasticity, the variation in particle size had little influence on the compressive strength and on the modulus of rupture and the curing time had little influence on all properties studied. In comparison with the reference geopolymer, it was observed that the replacement of 10.50% of sand by rubber residue with only coarse rubber and 14.50 days of cure presented a reduction in compressive strength of 20.41%, 12.18 % in water absorption, 13.73% in void index, 1.76% in specific mass and increase of 15.08% in modulus of rupture, 1.50% in modulus of elasticity and 95.76% in toughness. With scanning electron microscopy it was observed that the increase in the dimensions of the rubber residue caused a decrease in the amount of pores in the matrix, corroborating with the analysis of the void index, it was also observed a reduction in the number of cracks with the increase in the rubber content , corroborating with the analysis of tenacity, which can change the rupture behavior of the composite from brittle to ductile. With the XRD it was observed that the geopolymer matrix is composed of crystalline phases and that there was no significant variation in its composition, even with variation in curing time and residue content. The geopolymer composite with rubber can be used in various applications such as: concrete or precast elements for civil construction.